Late Miocene paleoenvironment of the Lambert Graben embayment, East Antarctica, evident from: Mollusc paleontology, sedimentology and geochemistry - Whitehead, JM; Ehrmann, W; Harwood, DM; Hillenbrand, CD; Quilty, PG; Hart, C; Taviani, M; Thorn, V; McMinn, A (Global and Planetary Change, 2006)
The Upper Miocene (10.7-9.0 Ma) Battye Glacier Formation was deposited 250 km inland from the modern Amery Ice Shelf edge in Prydz Bay, East Antarctica. The composition of clay minerals distinguishes a Lower Member, which reflects regional erosion of Precambrian metamorphic basement, from an Upper Member, which records increased erosion of local Permian-Triassic Amery Group strata. The Upper Member was deposited in an ice-proximal environment akin to the modern fjords of East Greenland, with substantial diamict deposition resulting from melting iceberg discharge. The Lower Member was deposited in an ice-distal environment and included the accumulation of the fossil-bearing McLeod Beds. The McLeod Beds contain much siliceous biogenic sediment ( 15% opal), which is rare to absent in the predominantly hemipelagic mud of modern East Greenland fjords. The McLeod Beds also contain largely monospecific in situ Hiatella sp. mollusc assemblages suggestive of environmental stress, potentially caused by low salinity melt-water and a high input of terrigenous sediment, which excluded most other benthic taxa. Geochemical results from primary aragonite in Hiatella shells imply large freshwater input into the marine environment during mollusc growth, causing low 18O, Na, Mg and high Fe values. The present study indicates that iceberg melt-water influence entering the marine environment was greater during the Late Miocene than today around Antarctica, and documents the paleoenvironment associated with a discrete period of ice margin retreat and marine incursion into the Lambert embayment. 2006 Elsevier B.V. All rights reserved.